2020
DOI: 10.7717/peerj.8319
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis breakdown duration in cattle herds: an investigation of herd, host, pathogen and wildlife risk factors

Abstract: Background Despite rigorous controls placed on herds which disclose ante-mortem test positive cattle to bovine tuberculosis, caused by the infection of Mycobacterium bovis, many herds in Northern Ireland (NI) experience prolonged breakdowns. These herds represent a considerable administrative and financial burden to the State and farming community. Methods A retrospective observational study was conducted to better understand the factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Both survival and case-control studies showed that a countylevel herd prevalence above 0.2% in the year prior to the start of the bTB breakdown was significantly associated with an increased risk of experiencing chronic bTB breakdowns. This result is in agreement with previous studies that identified proximity to infected neighbors as a risk factor for persistent bTB infection in Spain (18) and Ireland (14) or prolonged outbreak duration in Northern Ireland (10,36). Local sources of infection that could contribute to this effect include local movements (51), contact with infected cattle and wildlife reservoirs (52), or environmental sources of M. bovis (53), thus contributing to disease recurrence or local persistence (6,12,54).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both survival and case-control studies showed that a countylevel herd prevalence above 0.2% in the year prior to the start of the bTB breakdown was significantly associated with an increased risk of experiencing chronic bTB breakdowns. This result is in agreement with previous studies that identified proximity to infected neighbors as a risk factor for persistent bTB infection in Spain (18) and Ireland (14) or prolonged outbreak duration in Northern Ireland (10,36). Local sources of infection that could contribute to this effect include local movements (51), contact with infected cattle and wildlife reservoirs (52), or environmental sources of M. bovis (53), thus contributing to disease recurrence or local persistence (6,12,54).…”
Section: Discussionsupporting
confidence: 92%
“…Herds with ≤2 bTBpositive herd tests were not considered to select the threshold in order to focus on problematic herds. The median bTB breakdown for all bTB-positive herds in Castilla y Leon duration was 133 days, which is in agreement with values reported in Northern Ireland (10,36).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…not only a source of infection to cattle—the ‘target’ host—but able to maintain infection without reintroduction from cattle) 2 , 9 , and even less is known about the role of badgers in cattle infection in the Edge Area. Thus the expansion of the cattle epidemic in the Edge Area could be the result of cattle-to-cattle, badger-to-badger, cross species transmission, or, indeed, other even less well-understood transmission routes such as through soil and farm waste 10 13 ; and the relative contributions of each potential transmission route, or if they differ between regions in the Edge Area, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recrudescence of infection is a known feature of bTB epidemiology in the UK and Ireland [ 14 , 15 , 16 , 17 , 18 , 19 ], and elsewhere [ 20 , 21 , 22 , 23 ]. Herds that experience a breakdown (that is, when one or more animals present with evidence of bTB via antemortem tests or postmortem surveillance) tend to be at a greater risk of future breakdown.…”
Section: Introductionmentioning
confidence: 99%